Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar pada Pembelajaran Bahasa Indonesia Berbasis Literasi Digital pada Kurikulum Merdeka - Kusumasari, Ervita Dwi; Sumarno, Sumarno; Dwijayanti, Ida (Medan Resource Center, 2024)
In the 21st-century education era, learning models that enhance critical thinking, collaboration, communication, and creative thinking skills are essential. Digital-based learning, specifically digital literacy, equips students not only with knowledge but also with the ability to apply their understanding in real-life situations, particularly for elementary school students. This study aims to optimize the process of improving 21st-century skills among elementary school teachers. Using instruments such as analysis documents (student self-reports during PBL implementation), 21st-century skills rubrics, and teacher questionnaires, the research seeks to provide a comprehensive description of the role of digital-based learning in enhancing these skills. The findings indicate that digital-based learning significantly supports the development of critical thinking, collaboration, communication, and creative thinking skills. Furthermore, this research offers valuable insights into the integration of digital-based learning in the independent curriculum for elementary schools, serving as a reference for Indonesian language learning.